Maldives : Public Sector Accounting and Auditing, A Comparison to International Standards - World Bank (World Bank, Washington, DC, 2012)
This assessment of public sector accounting and auditing standards is generally meant to assist with the implementation of more effective public financial management (PFM) through better quality accounting and public audit processes in Maldives. It is intended to provide greater stimulus for more cost-effective outcomes of government spending. The specific objectives are (a) to provide the country's accounting and audit authorities and other interested stakeholders with a common well-based knowledge as to where local practices stand in comparison with internationally developed standards of financial reporting and audit; (b) to assess the causes of the prevailing variances; (c) to chart paths to reduce the variances; and (d) to provide a continuing basis for measuring improvements. Annex A explains the methodology used for the study. Annex B provides a summary of international accounting and auditing standards referred to in this study. Annex C and D provide country accounting and auditing legislation, respectively. Lastly, Annex E includes a description of the benefits of accrual accounting. The World Bank is supporting initiatives to develop local systems so that donors can increase their use of country systems for their own grants and loans.